O17.5 Declining trends in anogenital warts since HPV vaccine introduction in a large urban health system, 2013–2017. (14th July 2019) - Yakely, Anthony; Oliviera, Carlos; Niccolai, Linda
Abstract : Background: Assessing the extent to which the HPV vaccines are affecting trends of HPV-related diseases is an important public health priority. Diagnoses of anogenital warts (AGW) provide an early indicator of vaccine impact due to its short incubation period compared to other HPV-related diseases. We expand on previous trend studies by including recent data through 2017 that permit more robust assessments since the routine recommendations for male vaccination in 2011 in the United States. Methods: Electronic medical record data were abstracted from encounters that occurred in 8 Yale-New Haven Health system clinics between 2013–2017. Visits related to incident AGW were identified for each patient as the first occurrence of either having an AGW diagnosis code (ICD-9 078.11) or 'genital warts' as a reason for visit indicated by their medical provider. The annual proportion of visits related to incident cases of AGW was estimated among the number of patients who had at least one visit in that clinic per year. Trends overall, by sex, and by vaccine eligibility were analyzed using Cochran-Armitage tests and p<0.05. Results: A significant decline over time was observed in the proportion of visits for incident AGW overall (p-value<0.001, annual percent change (APC)=-20.3). When stratified by sex, a significant decline was observed in both males (p-value=0.0203, APC=-17.9) and females (p-value=0.0006 APC=-9.4). Significant declines were also observed among later birth cohorts that were eligible for HPV vaccines (p-value=0.0003, APC=-24.4) but not for earlier birth cohorts (p-value=0.12, APC=-3.1). Conclusion: Diagnoses of incident AGW have declined significantly through 2017, and birth cohort analyses are consistent with expected HPV vaccine impact. Importantly, these trends reflect and extend previous analyses and provide strong evidence of declines in males since their eligibility for routine vaccination in 2011 in the United States. Disclosure: No significant relationships.